DRAINAGE CAPABILITY AND WATER QUALITY OF KLONG RUNGSIT PRAYOONSAK - Saiyudthong, Chanwit (Srinakharinwirot University Journal of Sciences and Technology, 2022)
In Bangkok flooding protection, Klong Rungsit is often used to divert water from the Chao Phraya River to the Nakhon Nayok River in wet season while in dry season Klong Rungsit receives domestic wastewater that has been increasing. With these 2 duties of Klong Rungsit, if there is a management tool to find the capability of the canal in diversion, it should be interested. This research employed Hec-Ras as a tool to determine suitable flow rates for Klong Rungsit. The elevations along the canal were surveyed and then input to Hec-Ras to simulate scenarios by varying the flow rates of 9, 18, 27, 36, 45, 54, 63 and 72 m3/s at the Manning’s values (n) of 0.015, 0.020 and 0.025 for downstream water level 2.0 and 3.0 m. From the simulation, it was found that if the downstream water level 3.0 m, flow rate 72 m3/s and n 0.025, water surface will overtop the right constructed levee. For the water quality of the canal, BOD around Klong 2 and 9 were more than 4.0 mg/L and classified as surface water quality type 4 that means it is not appropriate to all activities for everyday life.